Real World Pharmacological First Treatment Patterns of Patients With Parkinson Disease and Disease Duration: A Large-Scale Cohort Study Using an Health Maintenance Organization Database. Issue 5 (September 2021) - Faust-Socher, Achinoam; Gurevich, Tanya; Rozani, Violetta; Giladi, Nir; Hemo, Beatriz; Peretz, Chava
Abstract : Objectives: Real-world data were used to describe first antiparkinsonian drug (FAPD) prescription patterns among Parkinson disease (PD) patients and to evaluate disease duration until levodopa (L-DOPA) treatment and until death, as related to FAPD, by age group. Methods: The community-based cohort (2000–2012) included 6243 patients, members of an Israeli Health Maintenance Organizations. Time from FAPD purchase to 2 end points (L-DOPA purchase and death) was calculated. Cox regressions were used to estimate adjusted heart rate (HR) to either end point as related to FAPD type, by age group. Results: During a mean follow-up of 4.8 ± 3.2 years, one third of the cohort died. The percent of L-DOPA use as a start drug increased with age, whereas the percent of dopamine agonists (DAs) and monoamine oxidase inhibitor B inhibitor (MAO-BI) decreased with age. Younger women were treated more often with DA as a start drug compared with younger men. In ages of younger than 50 years, time to L-DOPA start in the initial DA-group was 4 times longer than in the initial MAO-BI group (HR, 0.23; 95% confidence interval, 0.08–0.43; 1/0.23, 4.35). All age groups exhibited a similar survival time trend associated with initial drug type. An age-pooled HR with initial L-DOPA-group as a reference group yielded that survival time was 2.4 times longer for the initial DA group (HR, 0.41; 95% confidence interval, 0.31–0.55; 1/0.41, 2.44), 1.9 times and 1.4 times for initial MAO-BI or amantadine, respectively. Conclusions: First antiparkinsonian drug choice might be associated with time until L-DOPA initiation but may represent disease severity at the time of prescription, thus also affecting survival time as well. Real-world data illustrated that this choice is also age and sex dependent.